Study of intake manifolds of an internal combustion engine: A new geometry based on experimental results and numerical simulations - Souza, Gustavo Rodrigues de; Pellegrini, Cláudio de Castro; Ferreira, Sérgio Lucas [UNESP]; Soto Pau, Felipe; Armas, Octavio (Elsevier, 2019)
During the intake period in internal combustion engines, it has been noted that the cylinder volume is not completely occupied due to the variation of specific volume and the pressure drop along the supply system. Consequently, the volumetric efficiency in the cylinder is lowered, negatively affecting the engine power output. In this paper, numerical and experimental studies were performed to investigate different geometries of intake manifolds of internal combustion engines, with the aim of improving its efficiency. The numerical solutions were obtained through a 1D commercial code (GT-Power®) which solves the one-dimensional equations of continuity, momentum and energy, using a finite volume scheme. An experimental set-up was built and mass flow rate and pressure measurements of the intake air were carried out. The set-up is composed by an internal combustion engine, driven by an electric motor, and the experiments were performed without fuel and combustion. Numerical and experimental results were compared and a good agreement was found, thus confirming that the commercial code used is capable of simulating the kind of phenomena studied. Based on the Helmholtz resonator effect theory, a new intake manifold geometry was proposed. Measurements showed the novel geometry to improve the volumetric efficiency of the engine by 6% at 3500 rpm, the more common speed for this kind of engine, consequently increasing the indicated power by 3.68 kW (4.93 hp). The observed increase is worthy of note, considering the inherent difficulty to improve the volumetric efficiency near its maximum value for this type of engine, occurring around 3000 rpm.
Keywords: 1D numerical simulation; Intake manifold; Internal combustion engine; Volumetric efficiency